Long-term patient-reported outcomes after anterior distraction osteogenesis of the maxilla in patients with cleft. Issue 1 (28th February 2023) - Yasin, Lina; Becker, Magnus; Svensson, Henry; Wiedel, Anna-Paulina
Abstract: Maxillary growth inhibition in patients with cleft lip and palate (CLP) is an undesired effect that may occur in the teens despite proper primary care. Dental malocclusion and distortion of facial appearance can be treated with external distraction osteogenesis (DO) of the maxilla. This entails a Le Fort I osteotomy, fastening a semi-circular distractor to the skull, distraction for three weeks, and fixation for three months before removal of the device. The aim of this descriptive long-term follow-up study was to evaluate DO of the maxilla from the patient-reported long-term perspective. Fourteen patients underwent a long-term follow-up including a questionnaire regarding their experience of DO. Sex, CLP diagnosis, age at DO and follow-up, and time required for active distraction and fixation were noted. Furthermore, documentation on rhinoplasty, lip plasty and velopharyngeal plasty after DO was registered. Objective results were assessed by a positive dental overjet in the front. Ten patients considered the distractor an everyday constraint, but all thought the procedure was worthwhile and would recommend it to others. Thirteen patients experienced improved bite and chewing, whereas one considered function unchanged. All were satisfied with their dental alignment. Three patients underwent a velopharyngeal plasty after DO. Moreover, six rhinoplasties and two lip plasties were performed. Despite a long and challenging treatment, teenagers and young adults with CLP and maxillary hypoplasia tolerate DO of the maxilla very well. Secondary measures to improve speech and appearance are often indicated.